Perencanaan Bangunan Penangkap Air Baku Sistem Penyediaan Air Minum (SPAM): (Studi Kasus Sungai Lambute, Kecamatan Abuki, Kabupaten Konawe, Sulawesi Tenggara) - Putranata, Irfan Najib; Assiddieq, Moch.; Adami, Aryani (Universitas Muhammadiyah Kendari, 2026)
This study examines the planning of a raw water catchment structure for the drinking water supply system (SPAM) of IKK Abuki, Konawe Regency. The problem in this study is that the existing intake of SPAM IKK Abuki was damaged due to flooding and the existing system uses pumping which requires high operational costs, therefore it is necessary to plan a raw water catchment structure in another location that is more effective. The purpose of this study is to obtain raw water sources in other locations that meet the quality and quantity requirements and to obtain a design for a raw water catchment structure. The method used to determine the quality of raw water is by bringing raw water samples to the laboratory for testing while for water quantity using the floating object method and current meter tools, for the design of the raw water catchment using literature studies, field measurements and autocad software. The results of this study indicate that the quality of the raw water source in the Lambute River meets the requirements for raw water sources with the characteristics of odorless, tasteless, color 5 TCU, TDS 30 mg/L, turbidity 10.5 NTU, temperature 27°C, pH 8.39, DO 5.35 mg/L. Meanwhile, for the quantity, the water discharge results obtained using the floating object method were 89 L/sec. and the current meter method was 27 L/sec., for the clean water needs of Abuki District in the next 10 years it requires 25.60 L/sec. so that the Lambute River discharge is sufficient to be used as a raw water source. The design of the raw water catchment has dimensions of 1.5 m in length, 1.5 m in width, and 1 m in height.